RESPONSE OF CALIFORNIA PAPAYA SEED GROWTH AS A RESULT OF SUGARCANE COMPOST APPLICATION IN ALUVIAL SOIL - Kurnaisih ,; Siti Hadijah; Agus Hariyanti (Fakultas Pertanian Universitas Tanjungpura, 2020)
This study aims to determine the growth response of California papaya seeds and to find the best dose of sugarcane compost application for the growth of California papaya seeds. The study was conducted at the Campus of Tanjungpura University, Pontianak for 3 months. The method used was a field experiment with a Completely Randomized Design (CRD) pattern, consisting of 6 treatments, 4 replications and 3 samples. Treatment b1 = dosage 150 g / poly bag ≈ 5% sugarcane compost b1 = dose 225 g / polybag ≈ 7.5% sugarcane compost b3 = 300 g / polybag dose ≈ 10% sugarcane compost b4 = 375 g dose / polybag ≈ 12.5% sugarcane compost b5 = doses 450 g / polybag ≈ 15% sugarcane compost and b6 = 525 g dose / polybag ≈ 17.5% sugarcane compost in a composition of 3 kg media weight each. The observation variables were plant height, number of leaves, leaf chlorophyll content, stem diameter, root volume and plant dry weight. The results of this experiment proved that the use of 150 g / polybag sugarcane compost was an effective dose for the growth of papaya seeds. Keywords: alluvial, california papaya seeds, sugarcane compost.